Effects of marketing contracts and resource-providing contracts in the African small farm sector: Insights from oil palm production in Ghana - Anette Ruml; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2019)
Smallholder farmers in developing countries often suffer from high risk and limited market access. Contract farming may improve the situation under certain conditions. Several studies analyzed effects of contracts on smallholder productivity and income with mixed results. Most existing studies focused on one particular contract scheme. Contract characteristics rarely differ within one scheme, so little is known about how different contract characteristics may influence the benefits for smallholders. Here, we address this research gap using data from oil palm farmers in Ghana who participate in different contract schemes. Some of the farmers have simple marketing contracts, while others have resource-providing contracts where the buyer also offers inputs and technical services on credit. A comparison group cultivates oil palm without any contract. Regression models that control for selection bias show that resource-providing contracts increase farmers' input use and yield. Resource-providing contracts also incentivize higher levels of specialization and an increase in the scale of production. These effects are especially pronounced for small and medium-sized farms. In contrast, the marketing contracts have no significant effects on input use, productivity, and scale of production. The results suggest that resource-providing contracts alleviate market access constraints, while the marketing contracts do not.
Keywords: C21; O12; O13; Q12; Q13; 330; contract farming; contract characteristics; agricultural production; specialization; production investments; oil palm; Ghana